Alliance, Trust, and Loss: Experiences of Patients Cared for by Students in a Longitudinal Integrated Clerkship. (4th June 2019) - Flick, Robert J.; Felder-Heim, Caitlin; Gong, Jennifer; Corral, Janet; Kalata, Kathryn; Marin, Alejandro; Adams, Jennifer E.
Abstract : Purpose: The longitudinal integrated clerkship (LIC) model, which allows medical students to participate in comprehensive care of a panel of patients over time, is rapidly expanding due to recognized benefits to students and faculty. This study aimed to determine how LIC student contact affected patient experience and self-described health outcomes. Method: This qualitative case study used semi-structured patient interviews to understand the impact of LIC learners at the University of Colorado School of Medicine on patients at Denver Health. Patients with at least three encounters with an LIC student and over age 18 were selected. Thirty patients were invited to participate in 2016–2017; 14 (47%) completed interviews before the thematic analysis reached saturation. Four researchers independently analyzed interview transcripts and reached consensus on emergent categories and themes. Results: Six broad themes were identified: beginnings of a relationship, caring demonstrated by student, growing to trust student, reaching a therapeutic alliance, improvement of patient outcomes due to student involvement, and a sense of loss after students completed the LIC program. Conclusions: Patients deeply valued the therapeutic alliances built with LIC students involved in their care over time. These alliances led to improved patient experience, mitigation of perceived health system failures, and subjective improvement in health outcomes. Patients described a sense of loss at the end of the LIC when students were no longer involved in their care. Curricula that support students building longitudinal therapeutic relationships with their patients are an opportunity to improve patient experience while promoting students' professional development.